Les contenus « informatiques » et leur(s) reconstruction(s) par des élèves de CM2. Etude didactique - Cédric Fluckiger; Yves Reuter (Recherches en Éducation)
Within this issue of the Journal “Recherches en Éducation” dedicated to the different ways research deals with students in the digital ages, we focus in this article on relations between students at the end of primary school and computer science “contents”, organized within the B2i. This article, included in disciplines didactics, aims at characterizing these teaching contents and at drawing some facts of this relationship. Invoking the concept of “disciplinary consciousness”, we try to determine how students imagine these contents, rebuild an image of the contents, their utility or purposes. Students are therefore conceived here as didactic subjects, ie “computer science learners”. We first detail our question’s didactics inscription, then we question the disciplinary status of computer science related contents. Then we examine how students answer a questionnaire in order to study how they “rebuild” and “live” these contents